PENGARUH MEDIA PEMBELAJARAN VIDEO ANIMASI PADA PERKEMBANGAN ANAK SISWA SEKOLAH DASAR - Alfis Savinah Aulia; Puan Herliya Nabila; Ahmad Ahya Ubaidillah; Abdullah Zaim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the influence of animated videos as a learning medium for elementary school students through literature analysis of related scientific journals. The aim is to examine the impact of animated videos on cognitive, social-emotional, creativity, and learning interest development. The results of the analysis show the positive potential of animated videos in improving students' understanding and interest in learning by simplifying complex materials and increasing motivation and active participation. Animated videos have proven effective in making learning more interesting and easier to understand. However, the study also identified limitations, namely that most of the studies reviewed only focused on the cognitive aspect, reducing a comprehensive understanding of its impact on other aspects of development. Further research is needed to explore the long-term impact of animated videos on all aspects of child development in a comprehensive and balanced manner. Futuristic studies need to consider other factors that may influence the effectiveness of animated videos as a learning medium, as well as consider individual differences in students in responding to this learning medium. In conclusion, although animated videos are promising, further research is needed to ensure their effective and optimal use in supporting students' holistic development.